COMPARATIVE HISTOPATHOLOGICAL STUDY BETWEEN AMIKACIN AND TOBRAMYCIN GIVEN ALONE AND IN COMBINATION WITH CALCIUM GLUCONATE IN RABBITS - Abdulkarim Salih, Nadia; Hassan Salih, Karokh; Abbas, Duraid Abdulhady (European Scientific Journal, ESJ, 2014)
An experiment conducted to explore a histopathological comparison between tobramycin sulphate and amikacin sulphate, and to explore the role of calcium gluconate in antagonizing or reducing the main toxic side effects of tobramycin and amikacin like nephrotoxicity.The experiment was designed to study the effects of therapeutic and triple doses of tobramycin and amikacin alone, and with calcium gluconate in rabbits. This experiment lasted for one month and was divided into three periods (pretreatment period for 7 days, treatment period for 14 days and recovery period 7 days). The results showed that tobramycin and amikacin differ in their toxic effects potential at both therapeutic and triple doses. Tobramycin caused more pathological changes than that changes caused by amikacin, the main changes in renal tissue that caused by therapeutic dose of tobramycin are hydropic swelling of renal tubular epithelial cells ,vascular congestion of glomeruli ,while the triple dose of tobramycin caused shedding of renal tubular epithelial cells, formation of hyaline casts in tubular lumina , loss of brush border, hydorpic swelling of renal tubular epithelial cells, foci of moderate to heavy mixed acute and chronic inflammatory cell infiltration (in form of neutrophils, lymphocytes, plasma cells and occasional eosinophil). Pretreatment with calcium significantly improved the study to the levels almost similar to that of control group for both drugs, and gave complete protection from toxic effects of amikacin, and complete to partial protection with tobramycin accordingly with their doses.